2020
DOI: 10.1051/0004-6361/202039132
|View full text |Cite
|
Sign up to set email alerts
|

Gaia18aen: First symbiotic star discovered by Gaia

Abstract: Context. Besides the astrometric mission of the Gaia satellite, its repeated and high-precision measurements also serve as an all-sky photometric transient survey. The sudden brightenings of the sources are published as Gaia Photometric Science Alerts and are made publicly available, allowing the community to photometrically and spectroscopically follow up on the object. Aims. The goal of this paper is to analyze the nature and derive the basic parameters of Gaia18aen, a transient detected at the beginning of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…6). One pair has supposedly the interstellar origin and its velocity is used to put the lower limit on the distance to some symbiotic stars (see e.g., Merc et al 2020;Mikołajewska et al 2021). Our preliminary analysis of the spectroscopic data of AX Per confirmed that the other pair arises in the symbiotic system.…”
Section: Comparison With Ax Perseimentioning
confidence: 51%
See 1 more Smart Citation
“…6). One pair has supposedly the interstellar origin and its velocity is used to put the lower limit on the distance to some symbiotic stars (see e.g., Merc et al 2020;Mikołajewska et al 2021). Our preliminary analysis of the spectroscopic data of AX Per confirmed that the other pair arises in the symbiotic system.…”
Section: Comparison With Ax Perseimentioning
confidence: 51%
“…The values from the 2MASS catalogue were converted to the standard system of Bessell & Brett (1988) using the transformations of Carpenter (2001). Note that in the case of the S-type symbiotic star Gaia18aen, the extinction value based on the comparison of synthetic and observed NIR spectra of the cool giant was larger than the one from the dust maps (by about 0.2 mag, similar to Hen 3-860; Merc et al 2020).…”
Section: Reddeningmentioning
confidence: 99%
“…Assuming a blackbody spectrum and case B recombination, the fluxes of Hβ, He i 5876, and He ii 4686 lines require T h ∼ 100 kK (also indicated by the presence of weak [Fe vii] emission lines in the best-exposed spectra), and luminosity (within a factor of 2), L h ∼ 200 L (see, e.g. Merc et al 2020). The estimated luminosity is similar to the quiescent L h ≈ 220 L resulting from the emission line fluxes published by Mikołajewska et al (1997) corrected for the reddening and distance adopted in this study (Sect.…”
Section: Hot Component Activity and Jet Evolutionmentioning
confidence: 99%
“…Assuming a blackbody spectrum and case B recombination, the fluxes of Hβ, He i 5876, and He ii 4686 lines require T h ∼ 100 kK (also indicated by the presence of weak [Fe vii] emission lines in the best-exposed spectra), and luminosity (within a factor of 2), L h ∼ 200 L (see, e.g. Merc et al 2020). The estimated luminosity is similar to the quiescent L h ≈ 220 L resulting from the emission line fluxes published by Mikołajewska et al (1997) corrected for the reddening and distance adopted in this study (Sec.…”
Section: Hot Component Activity and Jet Evolutionmentioning
confidence: 99%